PELAKSANAAN PELAYANAN TERPADU SATU PINTU (PTSP) KEMENTERIAN AGAMA KABUPATEN LAMANDAU: TANTANGAN DAN STRATEGI PENYEMPURNAAN - Rozi, Fatkur; Irwani, Irwani; Yusuf, Muhammad (Jurnal Progress Administrasi Publik, 2025)
This article aims to present an overview of the One-Stop Integrated Service (PTSP) at the Lamandau District Office of the Ministry of Religious Affairs, established under Law No. 25/2009 on Public Services, and to examine its operational dynamics, including the challenges encountered and potential solutions. The Lamandau District Office of the Ministry of Religious Affairs has a PTSP policy with the aim of providing quality public services. The government office in Lamandau, West Sumatra, was chosen as the PTSP pilot site. A skilled workforce is essential for PTSP to provide its services. Interviews using empirical juridical techniques provided the data used in this article. According to this research, the PTSP process of the Lamandau District Office of the Ministry of Religious Affairs is not functioning properly. At the Lamandau District Office of the Ministry of Religious Affairs, the PTSP mechanism is constrained by space, personnel, and infrastructure issues. We hope to improve the standard of facilities, infrastructure, and human resources by providing assistance to impartial officers in online service planning and service processes.   Keywords: One Stop Integrated Service; Public Service.